Chemoresistance, Cancer Stem Cells, and miRNA Influences: The Case for Neuroblastoma - Alfred Buhagiar; Duncan Ayers (Analytical Cellular Pathology)
Neuroblastoma is a type of cancer that develops most often in infants and children under the age of five years. Neuroblastoma originates within the peripheral sympathetic ganglia, with 30% of the cases developing within the adrenal medulla, although it can also occur within other regions of the body such as nerve tissue in the spinal cord, neck, chest, abdomen, and pelvis. MicroRNAs (miRNAs) regulate cellular pathways, differentiation, apoptosis, and stem cell maintenance. Such miRNAs regulate genes involved in cellular processes. Consequently, they are implicated in the regulation of a spectrum of signaling pathways within the cell. In essence, the role of miRNAs in the development of cancer is of utmost importance for the understanding of dysfunctional cellular pathways that lead to the conversion of normal cells into cancer cells. This review focuses on highlighting the recent, important implications of miRNAs within the context of neuroblastoma basic research efforts, particularly concerning miRNA influences on cancer stem cell pathology and chemoresistance pathology for this condition, together with development of translational medicine approaches for novel diagnostic tools and therapies for this neuroblastoma.